Pengaruh Adjuvant Alumina dan Protein Rekombinan Fim-C Inclusion Bodies Salmonella Typhimurium terhadap Respon Imun Mencit Balb/C - Dian Larasati; Muktiningsih Nurjayadi; Kurnia Agustini (Jurnal Riset Sains dan Kimia Terapan, 2017)
Typhoid fever is one of the most public health problem in the world, with approximately 17 million cases of typhoid fever worldwide and 600,000 death cases each year. One method to prevent typhoid fever is vaccination. Nowadays, frequently, vaccine for typhoid fever is Ty 21a and vi polysaccharide vaccines. In other hands, it has side effect of nausea, fever, and headache. So it is still necessary to search other typhoid vaccine with minimum side effects. The purpose of this study was to obtain immunogenicity test information of recombinant protein Fim-C S. typhimurium and adjuvant alumina in Balb / C mice. The used doses were 20 Î¼g, 40 Î¼g, and 60 Î¼g. Plasma was obtain then analyzed by ELISA, western immunobloting, and dot blot. Immune response of Balb / C mice from KS 1 showed significant differences antibody when dose injection 40Î¼g / 20g BB and KS2 showed significant differences antibody when dose injection 20Î¼g / 20g BB compared with KN. Adjuvant alumina was added to the Fim-C protein inclusion bodies Salmonella typhimurium provides a higher immune response compared to the Fim-C inclusions bodies Salmonella typhimurium protein without the addition of adjuvant alumina. The results of analysis by using western blot and dot blot showed the formation of brown color indicating the interaction between protein Fim-C inclusion bodies Salmonella typhimurium and anti-Fim-C S. typhimurium antibodies. The results of adjuvant alumina and protein Fim-C inclusion bodies of Salmonella typhimurium in Balb / C mice concluded that adjuvant alumina and Fim-C protein inclusion bodies Salmonella typhimurium provide significant increased immune response in Balb / C mice. Keyword: Salmonella typhimurium, typhoid vaccine, recombinant protein Fim-inclusion Bodies S. typhimurium, Balb/C mice